THE RESPONSE OF THE MUNG BEANS PLANT (Vigna radiate L.) ON THE DOSAGE OF LEGIN AND MANURE - Deonisio Sequeira Araujo; Tutut Wirawati; Mofit Eko Poerwanto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
Aims of, the research were to discover the influence the legin (legume) inoculation and the manure dosage to the growth and yield of the mug beans. The research was conducted at the research station at Wedomartani, District of Sleman, the Special Region of Yogyakarta. From June up to August 2018. Field experiment was arranged on the Randomized Complete Block Design with two factors, and repeated for three times. The first factor was legin application consisted of three levels, 9 g of legin/kg seeds, 12 g of legin/kg seeds, 15 g of legin/kg seeds. The second factor was cow manure dosage application consisted of five, dosage levels 0 ton/ha, 5 tons/ha, 10 tons/ha, 15 tons/ha, 20 tons/ha. The results of the research showed that the dosage of the manure had influence to the plant’s height and the leave’s chlorophyll. The best dosage of the manure is 10 tons/ha. The dosage of legin had influence on the plant’s height, leave’s chlorophyll, number of nodules, number of pods per plant, weight of sun dried seeds per plant, weight of sun dried seeds per plot, weight of 100 seeds and weight of sun dried seeds in ton/ha. The best dosage of the legin wais 15 g legin/kg seeds. The damage level of the plant did not influenced by the dosage of manure and legin. There was no interaction between the dosage of manure and legin in all observed parameters.Keyword: Mug beans, legin, cow manure.